Method for determining the integrated value of a construction project - Nakhimi, M.; Savina, O.; Haidaienko, O.; Bielova, O.; Бєлова, Олена Ігорівна (Scientific heritage, 2021)
This work is devoted to the peculiarities of using an integrated approach in the management of construction projects. It was shown that the integrated approach is used as a combination of the value approach with the man agement of the content of construction projects into a single integrated process. The processes of operation of these two control methods are considered and a simplified diagram of possible interaction is built. A simpler way of constructing a diagram for integration of value content management of construction projects was presented as a factor in establishing a clear connection to achieve project goals, in this case, time, value (costs) and content (resources)
Keywords: project content management; project management; construction project management; WBS; construction projects